Implementasi Tantangan Ajaran Tri Kaya Parisudha Di Era Digital - Ni Putu Ayu Dian Puspa W; Ni Wayan Selina Dewi; I Made Hartaka (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2022)
In the digital era like today, there are many preparations that must be owned apart from infrastructure, as well as character readiness to face various kinds of reforms, changes and challenges that accompany developments in this digital era. Because in this digital era it will open cultural distinctions that allow various types of culture to enterthe midst of people’s lives which will result in conflicts between religion, customs and culture that lead to eastern culture which is the basic foundation of Indonesian people’s life. Which will be very contrary to religion, customs and eastern culture which is the basic foundation of Indonesia social life. The development of technology and the entry of the digital world into almost all lines of life, have changed many things, including human behavior. The digital age changes the way people think when they are doing something. Digital culture is also something that shapes the way we interact, behave, think and communicate in a society that uses internet technology. Digital culture that is growing rapidly in everyday life is inseparable and cannot be separated from the activities carried out by humans, where every second there are so many technologies that are developing rapidly. Digital technology has changed the way people in Indonesia interact with each other, with the media or other things related to Indonesia culture. Culture is also formed from several elements, namely religious and political systems, customs, customs, language, clothing/appearance, works of art and others it is undeniable, the development of the digital world has targeted all sides of life. The side of human life that is not affected by the digitization process.